Enrichment and determination of Ni2+ ions in water samples with a diamino-4-(4-nitro-phenylazo)-1H-pyrazole (PDANP) by using FAAS - Ciftci, H.; Yalcin, H.; Eren, E.; Olcucu, A.; Sekerci, M. (Elsevier Science Bv, 2010)
Nickel, as a heavy metal, is toxic for many living species. Thus, the determination of trace amounts of nickel in environmental samples is of great importance. In the present study, new, sensitive, simple and validated solid phase extraction method is developed for the determination of nickel. In recent study nickel was preconcentrated as diamino-4-(4-nitro-phenylazo)- 1H-pyrazole (PDANP) chelates (Ni-PDANP) from sample solutions using a column containing Amberlite XAD-7 and determined by flame atomic absorption spectrometry (FAAS). The optimum experimental parameters such as pH of the medium, sample flow rate, eluent and effect of matrix ions on the method efficiency were investigated. The optimum pH value for quantitative sorption of Ni-PDANP was found between 6.0 and 8.0. Elution process was performed by using 6 mL of 2 mol L-1 HCl. The sorption capacity of resin was determined to be 7.2 mg g(-1) for Ni. The preconcentration factor was 125. In optimized conditions. A relative standard deviation and detection limit were found to be 2.8% and 0.44 mu g L-1 respectively. The method was successfully applied to determine the trace amounts of nickel in tap water and mineral waters, and suitable recoveries were obtained (100.0-103.5%). (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Solid phase extraction; Amberlite XAD-7; PDANP; Nickel; Preconcentration; FAAS